Driving Green Investments by Measuring Innovation Impacts. Multi-Criteria Decision Analysis for Regional Bioeconomy Growth - Fabiana Gatto (MDPI AG, 2021)
Regional policies play a pivotal role in green transition and pursuing the European Green Deal decarbonization targets. Despite the general recognition of the strategic value of the bioeconomy in realizing this challenge, regional roadmaps for its growth are not yet a widespread tool in local innovation policy. Conversely, driving green investments by measuring the innovation potential of the bioeconomy could shape a low-carbon economy by leveraging the full potential of local resources. In order to validate a replicable decision-making model driving 2021–2027 ERDF funds towards this mission, this paper measures the economic, social and technological impact of the Lombard bioeconomy through five applications and eight criteria. The methodology allows quantification of the local bioeconomy value and, through a Multi-Criteria Decision Analysis (MCDA), identifies the bio-based applications with the highest innovation potential. By measuring the current and prospective impact of the bioeconomy, Bio-chemicals, Agri-foods, and Biopolymers emerges as the applications with the highest innovation potential rate for Lombardy. Five recommendations to drive green investments and shape the regional roadmap for the bioeconomy are finally defined, providing a tool for industrial applications with a greater impact on local competitiveness.